Soimenski, nominaten ali nominotipski? - prispevek k sistematskemu poimenovanju - Trontelj, Peter (Acrocephalus, 2006)
The use of the terms nominate, nominotypical, and a Slovenian translation thereof is discussed. Despite the prevalence of populational and tree thinkingover typological essentialism, there is an ongoing need for the designation of subordinate type taxa or specimens in biological taxonomy. Therefore, it remains of some importance to use the correct term for a subordinate taxon containing the name-bearing type, e.g. in the subspecies within a species. The appropriate term to denote such a subspecies is nominotypical. However, throughout the ornithological literature the old version nominate or even a misspelling thereof (nominant) seems to persist.
Keywords: ornitologija; strokovna terminologija